THE EFFECT OF BUDGET PARTICIPATION ON MANAGERIAL PERFORMANCE WITH COST MANAGEMENT KNOWLEDGE AS A MODERATED VARIABLES - Kristiani, Sharon (Fakultas Bisnis Universitas Katolik Widya Mandala Surabaya, 2021)
This study empirically examines the effect of budget participation on managerial performance and the moderating effect of cost management knowledge on the effect of budget participation on managerial performance. The population and sample in this study are middle and lower-level managers in manufacturing companies in East Java, Indonesia, who met the criteria. The sampling technique was convenience sampling with a sample of 83 people. The research hypothesis was tested using multivariable regression analysis. The results showed that the higher the level of budget participation, the higher the managerial performance. The high level of participation is accompanied by the high knowledge of managers about cost management affecting managerial performance. Thus, this research shows that budget participation affects managerial performance. Further research on the variable cost management knowledge found that knowledge of cost management as a quasi-moderator moderates the relationship between budget participation and managerial performance.